Comparison of Super Mini Percutaneous Nephrolithotomy (smPCNL) and Extracorporeal Shock Wave Lithotripsy (ESWL) in Pediatric 1-2 cm Kidney Stones: A Single-Center Retrospective Controlled Study - SEVİM, Mehmet and Demir, Murat and Eryılmaz, Recep and Aslan, Rahmi and Taken, Kerem (Urology Journal, 2026)
Purpose: To compare outcomes of super mini percutaneous nephrolithotomy (smPCNL) with extracorporeal shock wave lithotripsy (ESWL) for stones 1-2 cm. Materials and methods: After receiving ethics committee approval for this study (Date: 10/09/2021 Decision No: 2021/10-01), the files of patients who underwent smPCNL and ESWL for kidney stones between January 2017 and June 2021 by the Urology Department of Van YYU Dursun Odabaşı Medical Center were retrospectively scanned. A total of 300 patients’ data were scanned retrospectively. After applying the exclusion criteria and omitting ESWL patients whose sessions were not completed, a total of 159 patients, including 82 in the ESWL group and 77 in the smPCNL group, were included in our study. Results: The mean age in the ESWL group was 6.72 ± 3.71, and the mean age in the smPCNL group was 6.63 ± 3.59 (range: 1-18 years). There was no significant difference in the age profile between the groups (p = .87). Regarding the direction of the stone procedure in the smPCNL group, the procedure was performed on the right side in 42 patients (54.54%) and on the left side in 35 patients (45.46%). In the ESWL group, the procedure was performed on the right side in 38 patients (46.35%) and on the left side in 44 patients (53.65%). No statistically significant difference was found between the groups in terms of side direction (p = .38). The mean body mass index (BMI) in the ESWL group was 20.10 ± 2.01, while it was 20.23 ± 2.05 in the smPCNL group. No statistically significant difference was observed between the two groups in terms of BMI (p =.68). The mean stone size in the ESWL group was calculated as 13.74 ± 1.91 mm (10-20 mm) and 149.75 ± 45.46 mm², which would provide more accurate results. The mean value in the smPCNL group was 14.06 ± 2.6 mm (10-20 mm) and 150.87 ± 50.34 mm². No statistically significant difference was found between the groups in terms of stone size (p(mm)=.37, p(mm²)=.88). Among 82 patients treated with ESWL, 21 (25.6%) were stone-free after the first session, increasing to 40 (48.8%) by the end of the second session, and to 50 (61.0%) at the end of the third session. In terms of sedoanalgesia, 19 patients (23.20%) were exposed to 1 session, 16 (19.5%) were exposed to 2 sessions, and 31 (37.80%) were exposed to 3 sessions. Sixteen (19.5%) patients did not receive anesthesia. When evaluated in terms of the need for re-intervention, it was observed in 22 patients (26.8%) in the ESWL group and 4 patients (5.2%) in the smPCNL group (p = .0003). In the comparison of the stone-free rate of the smPCNL and ESWL groups, a statistically significant difference was observed in both the early and late periods (p = .001). When comparing the early and late periods of smPCNL (p = .79) and ESWL (p = .19) within their own groups, no statistical difference was observed. When smPCNL and ESWL were classified according to the Clavien-Dindo classification in terms of complications, no statistically significant difference was observed (p = .51). Conclusion: ESWL remains the preferred first-line option for many pediatric patients due to its safety and non-invasive nature. However, smPCNL provides higher single-session stone-free rates for 10–20 mm renal stones and may reduce repeated anesthesia exposure. SmPCNL should be considered a viable first-line alternative to achieve higher stone-free rates without increasing complication risks. Prospective, multicenter randomized trials are warranted.